Women Empowerment through Muslim Architecture Which Built by Name of them in Bangladesh during Mediaeval Period: A Preliminary Survey Report - Islam, Sk. Zohirul (American Economic & Social Review, 2018)
There are many Muslim architectures built by women patron which called Bibi/Begum in Bangladesh during mediaeval period as Binat Bibi Mosque architecture at Dhaka. It mentioned women’s contribution financially. This research paper is trying to show women empowerment through architecture which built by name in Bangladesh during mediaeval era. It is a preliminary qualitative survey report and tries to understand how housewives inspired to makes/commissioned for constructing monuments. Besides, what was the position of them in the Royal court or their society as well as Bibi/Begum contribution in mediaeval Muslim mosque architecture of Bengal and by name monuments of tomb architecture formation?